Clinical and radiographic outcomes of upper thoracic versus lower thoracic upper instrumented vertebrae for adult scoliosis: a meta-analysis - X. Kang (Brazilian Journal of Medical and Biological Research, 2018)
The aim of this study was to evaluate the clinical and radiographic outcomes of upper thoracic (UT) versus lower thoracic (LT) upper instrumented vertebrae (UIV) for adult scoliosis by meta-analysis. We conducted a literature search in three databases to retrieve related studies up to March 15, 2017. The preliminary screened studies were assessed by two reviewers according to the selection criteria. All analyses were carried out using the statistical software package R version 2.31. Odds ratios (OR) with 95% confidence intervals (CI) were used to describe the results. The I2 statistic and Q statistic test were used for heterogeneity assessment. Egger's test was performed to detect publication bias. To assess the effect of each study on the overall pooled OR or standardized mean difference (SMD), sensitive analysis was conducted. Ten trials published between 2007 and 2015 were eligible and included in our study. Meta-analysis revealed that the UT group was associated with more blood loss (SMD=0.4779, 95%CI=0.3349-0.6209, Z=6.55, P<0.0001) and longer operating time (SMD=0.5780, 95%CI=0.1971-0.958, Z=2.97, P=0.0029) than the LT group. However, there was no significant difference in Oswestry Disability Index, Scoliosis Research Society (SRS) function subscores, radiographic outcomes including sagittal vertical axis, lumbar lordosis, and thoracic kyphosis, length of hospital stay, and revision rates between the two groups. No evidence of publication bias was found between the two groups. Fusion from the lower thoracic spine (below T10) has as advantages a shorter operation time and less blood loss than upper thoracic spine (above T10) in posterior long-segment fixation for degenerative lumbar scoliosis.